Legal Review of Ferdy Sambo Decision From the Perspective of Justice of the Offender - Riskiqa Sekarsari, Nesha Sarah; Puluhulawa, Jufryanto (Estudiante Law Journal, 2024)
Abstract: The purpose of the research is to find out what factors influence the imposition of sanctions for illegal mining crimes in decision No. 177/Pid.Sus/2022/PN Gto. The research method used in this research is the normative research method by taking a statutory approach. The results of this study Illegal mining has a detrimental impact, both for official permit holders and the environment. Perpetrators of illegal mining can be subject to criminal sanctions in accordance with the provisions in Law Number 4 of 2009 concerning Mineral and Coal Mining. Criminal sanctions that can be given include imprisonment and fines. The factors that influence the decision of Decision Number 177/Pid.Sus/2022/PN Gto are laws and regulations, violation of the law, involvement of the defendant, absence of a valid permit, level of loss and environmental impact, and mitigation factors.